2010
DOI: 10.3389/fnbeh.2010.00022
|View full text |Cite
|
Sign up to set email alerts
|

The rewarding nature of social interactions

Abstract: The objective of this short review is to highlight rewarding aspects of social interactions for humans and discuss their neural basis. Thereby we report recent research findings to illustrate how social stimuli in general are processed in the reward system and highlight the role of Theory of Mind as one mediating process for experiencing social reward during social interactions. In conclusion we discuss clinical implications for psychiatry and psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 36 publications
(46 reference statements)
1
105
0
Order By: Relevance
“…In the social domain, findings from studies comparing social and non-social stimuli (Perry, A., Stein, L., & Bentin, S., 2011;Perry, Troje & Bentin, 2010;Pineda & Hecht, 2009), with the aim of deconstructing the social relevance of the mirror motor system, could be accounted for by the intrinsic reward that may be associated with social stimuli and social interaction, as opposed to stimuli devoid of any social meaning or value that may be inherently less rewarding. In other words, the social interaction in itself may be rewarding to the observer, as suggested by some authors (Krach, Paulus, Bodden, & Kircher, 2010). This may also be relevant to studies which have found that the social relationship between the observer and the performer may influence mirror neuron activity (Liew, Han, & Aziz-Zadeh, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…In the social domain, findings from studies comparing social and non-social stimuli (Perry, A., Stein, L., & Bentin, S., 2011;Perry, Troje & Bentin, 2010;Pineda & Hecht, 2009), with the aim of deconstructing the social relevance of the mirror motor system, could be accounted for by the intrinsic reward that may be associated with social stimuli and social interaction, as opposed to stimuli devoid of any social meaning or value that may be inherently less rewarding. In other words, the social interaction in itself may be rewarding to the observer, as suggested by some authors (Krach, Paulus, Bodden, & Kircher, 2010). This may also be relevant to studies which have found that the social relationship between the observer and the performer may influence mirror neuron activity (Liew, Han, & Aziz-Zadeh, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…These areas have been associated with social reward (Krach et al . ), emotional empathy (Abu‐Akel & Shamay‐Tsoory ; Fan et al . ), cognitive empathy (CE) and theory of mind (ToM; Gallagher & Frith ; Blair ; Vollm et al .…”
Section: Introductionmentioning
confidence: 99%
“…These effects may involve in increase anxiety and depression. The positive effects of social interaction are dependent on reward center (Krach, Paulus, Bodden, & Kircher, 2010). Of hormonal factors, oxytocin is the most putative hormone.…”
Section: Discussionmentioning
confidence: 99%